Aligning in and through interaction: Children getting in and out of spontaneous activity. (December 2014) - Rendle-Short, Johanna; Cobb-Moore, Charlotte; Danby, Susan
Spontaneous play, important for forming the basis of friendships and peer relations, is a complex activity involving the management and production of talk-in-interaction. This article focuses on the intricacies of social interaction, emphasizing the link between alignment and affiliation, and the range and importance of verbal and nonverbal interactive devices available to children. Analysis of the way in which two girls, one of whom has been diagnosed with Asperger's Syndrome, engage in spontaneous activities demonstrates the potential for interactional difficulty due to the unscripted nature of the interaction. The article argues for further research into how improvised, unscripted interactions are initiated within moment-by-moment talk, how they unfold, and how they are brought to a close in everyday contexts in order to understand how children create their social worlds.